Non-motor symptoms in multiple system atrophy: A comparative study with Parkinson's disease and progressive supranuclear palsy - Hu, Wen-Zheng; Cao, Ling-Xiao; Yin, Jin-Hui; Zhao, Xue-Song; Piao, Ying-Shan; Gu, Wei-Hong; Ma, Jing-Hong; Wan, Zhi-Rong; Huang, Yue (Frontiers in Neurology, 2023)
Background Non-motor symptoms (NMS) are compulsory clinical features for the clinical diagnosis of multiple system atrophy (MSA), some of which precede motor symptoms onset. To date, few studies have systematically investigated NMS in MSA and the timing of presenting NMS as the disease progresses. Clinically, MSA is difficult to be differentiated from Parkinson's disease (PD) and progressive supranuclear palsy (PSP), and the differences in NMS between MSA and PD/PSP remain unclear. The aim of this study was to compare the burden of NMS between MSA and PD/PSP and to delineate the timing of NMS presentation relative to the onset of motor symptoms in MSA. Methods A total of 61, 87, and 30 patients with MSA, PD, and PSP, respectively, were enrolled in this study. NMS was systematically assessed in all patients using the NMS scale (NMSS), and the onset of NMS relative to the onset of motor symptoms in MSA was investigated. Results MSA group had higher total NMSS scores (82.15 ± 46.10) than the PD (36.14 ± 30.78) and PSP (50.30 ± 55.05) groups (p < 0.001 overall). The number distribution pattern of the NMS was significantly different among the three parkinsonian disorders (p < 0.001 overall). In total, 85.2% of patients with MSA had more than 10 NMS, which was significantly higher than PD (28.7%) and PSP (33.3%). The frequency and scores of many NMSS subdomains and symptoms were higher in MSA than in PD and PSP (all p < 0.05). Multivariate logistic regression analysis revealed that patients with fainting, lack of motivation, swallowing, and loss of sexual interest could be attributed to MSA rather than PD or PSP, while patients with loss of concentration and forgetfulness were characteristic features of PD or PSP rather than MSA. REM-sleep behavior disorder (RBD), constipation, problems having sex, and loss of sexual interest preceded the motor symptoms onset of MSA by 2.81 ± 4.51, 1.54 ± 6.32, 1.35 ± 4.70, and 0.45 ± 3.61 years, respectively. Conclusion The NMS spectrum in MSA differs from that of PD and PSP. Patients with MSA have a higher NMS burden than patients with PD or PSP. RBD, constipation, problems having sex, and loss of sexual interest may become early diagnostic clinical markers of MSA.